Protocol for Anesthesia Animal Model in Biomedical Study - Rachmat Hidayat; Patricia Wulandari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Recognition of pain depends upon intact pathways from pain receptors to the thalamus and cerebral cortex, as well as functional cerebral cortex and subcortical structures. Thus any means that renders the cerebral cortex nonfunctional, such as hypoxia or drug depression, prevents pain. When this happens, stimuli that evoke motor nerve reflexes that may be painful to the conscious animal are not painful in the unconscious animal. Equally painful stimuli administered to animals chemically paralyzed by curare or succinylcholine will not evoke a motor reflex simply because of paralysis, but will cause pain because of the conscious state. Hence, it is possible that unconscious animals may feel no pain but respond to certain stimuli, and paralyzed animals may feel pain but cannot respond.